Saline wastewater treatment by Chlorella vulgaris with simultaneous algal lipid accumulation triggered by nitrate deficiency. (October 2015) - Shen, Qiao-Hui; Gong, Yu-Peng; Fang, Wen-Zhe; Bi, Zi-Cheng; Cheng, Li-Hua; Xu, Xin-Hua; Chen, Huan-Lin
Highlights: C. vulgaris was found suitable for saline wastewater treatment. Salinity was essential for lipid accumulation of C. vulgaris . Lipid content was boosted at point of nitrate deficiency by Nile red method. High nutrient removal efficiencies could be obtained by recycling cultivation mode. Pollutants in a real tidal saline water were efficiently utilized by microalgae. Abstract: Chlorella vulgaris, a marine microalgae strain adaptable to 0–50 g L −1 of salinity, was selected for studying the coupling system of saline wastewater treatment and lipid accumulation. The effect of total nitrogen (TN) concentration was investigated on algal growth, nutrients removal as well as lipid accumulation. The removal efficiencies of TN and total phosphorus (TP) were found to be 92.2–96.6% and over 99%, respectively, after a batch cultivation of 20 days. To illustrate the response of lipid accumulation to nutrients removal, C. vulgaris was further cultivated in the recycling experiment of tidal saline water within the photobioreactor. The lipid accumulation was triggered upon the almost depletion of nitrate (<5 mg L −1 ), till the final highest lipid content of 40%. The nitrogen conversion in the sequence of nitrate, nitrite, and then to ammonium in the effluents was finally integrated with previous discussions on metabolic pathways of algal cell under nitrogen deficiency.